Konservasi Ex Situ Kantong Semar (Nepenthes sumatrana (Miq) Beck) pada Beberapa Media Tanam Menggunakan Metode Split Anakan - Ryan Budi Setiawan; Rizah Rizwana Wahyuni; Arif Kurniawan (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2017)
Nepenthes is a unique plant in Indonesia whose existence is endangered and almost extinct, so that conservation efforts are required both in situ and ex situ. Vegetative propagation by separating tiller is one method that can be done, using a porous planting medium resam form of roots, husk, cocopeat and moss. The purpose of this study is to obtain the best media for breeding puppies Nepenthes (Nepenthes Sumatrana (Miq) Beck). The experiment is based on a randomized block design (RAK) to use the media's treatment plant that consists of 5 level and 3 experimental groups, the level of treatment trials include: M1 = root resam, M2 = husk, M3 = cocopeat, M4 = moss, M5 = combination of charcoal husk, cocopeat, resam roots and moss with a volume ratio of 1: 1: 1: 1. The observations are the following variables: plant height increment, increment the number of leaves, the length of leaves, leaf width increase, in the number of pitcher, pitcher the length and the length of roots. The results showed the best medium that can increase the number of leaves and number of pockets of most plant Nepenthes Sumatrana (Miq) Beck is the root media resam by increments of 4.55 strands and 2.77 pitcher. While the best medium that can enhance the long pitcher of Nepenthes sumatrana (Miq) Beck is a media combination with increasing 2.02 cm.